Protocol for the purification and analysis of nuclear UFMylated proteins - Pudchalaluck Panichnantakul; Marlene Oeffinger (STAR Protocols)
Summary: Protein UFMylation regulates numerous cellular processes including ribosome quality control and nuclear DNA repair. Here, we present a technique to isolate nuclei and purify UFMylated proteins under denaturing non-reducing conditions from commonly used mammalian cell line models such as hTERT-RPE1, HEK293, U2OS, and HCT116 cells. We then describe procedures for identifying and analyzing purified UFMylated proteins using mass spectrometry and western blot.For complete details on the use and execution of this protocol, please refer to Panichnantakul et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.